Inhibitory effect of Paliurus spina-christi Mill., Celtis tournefortii L. and Nigella sativa L. on N?-(Carboxymethyl) lysine in meatballs - Aydemir, Mehmet Emin; Arslan, Ali; Takim, Kasim; Altun, Serap Kilic; Yilmaz, Mustafa Abdullah; Cakir, Oguz (Elsevier Sci Ltd, 2024)
This study was conducted to examine the effect of cooking at different temperatures on the formation of N epsilon-(carboxymethyl) lysine (CML) after adding Paliurus spina-christi Mill. (PSC), Celtis tournefortii L. (CT) fruits, and Nigella Sativa L. (NS) seeds to the meatballs. Phytochemical and bioactivity properties were determined before adding PSC, CT fruits, and NS seeds to the meatballs. Then, PSC, CT fruits, and NS seeds were added to the meatballs at a rate of 2% and stored at 4 +/- 1 degrees C for 16 days. CML, TBARS, pH, and a(w) analyses were performed on the meatballs. The highest phytochemical and bioactivity levels were detected in PSC fruit. The a(w) values detected in the meatball groups were found to be between 0.931 and 0.951 on the 0th day and between 0.963 and 0.985 on the 16th day, and the pH values ranged from 5.66 to 6.06 on the 0th day and from 6.10 to 6.74 on the 16th day. TBARS values of the meatballs were found to be between 1.17 and 1.98 on day 0 and 1.70-3.34 mg MDA/kg on day 16. CML levels in the meatballs were determined to be between 11.15 and 13.45 on day 0 and between 13.43 and 18.17 mu g/g on day 16. The highest a* value was found in the meatballs with added CT fruit. It was determined that NS seeds had a negative effect on the a* value of the meatballs. In conclusion, adding PSC, CT fruits, and NS seeds can imbue meatballs with functional properties, thereby creating a more health-beneficial product for humans.
Keywords: Meatballs; N epsilon-(carboxymethyl) lysine; Paliurus spina-christi mill.; Celtis tournefortii L.; Nigella Sativa L